2014
DOI: 10.1080/13607863.2014.903468
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated to quality of life among nursing home patients with dementia

Abstract: Neuropsychiatric symptoms, apathy, severity of dementia, and impairment in activities in daily living are associated with reduced QOL in NH patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 46 publications
6
70
2
1
Order By: Relevance
“…These two studies failed to find a statistically significant association between cognitive status and QoL. As to the severity of dementia, only two studies (Marventano et al, 2015;Mjørud et al, 2014) explored its influence on QoL for elderly people with dementia. Both of them indicated that QoL for elderly people with dementia tends to decrease with increasing severity of dementia.…”
Section: Physical Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two studies failed to find a statistically significant association between cognitive status and QoL. As to the severity of dementia, only two studies (Marventano et al, 2015;Mjørud et al, 2014) explored its influence on QoL for elderly people with dementia. Both of them indicated that QoL for elderly people with dementia tends to decrease with increasing severity of dementia.…”
Section: Physical Factorsmentioning
confidence: 99%
“…15 studies (León-Salas et al, 2015;Garre-Olmo et al, 2012;Hodgson 19 et al, 2014;Salvador et al, 2000;Black et al, 2012;Beerens et al, 2014;Beer et al, 2010;Samus et al, 2005;Sloane et al, 2005;Winzelberg et al, 2005;Beerens et al, 2013;Missotten et al, 2007;Barca et al, 2011;Wetzels et al, 2010;Mjørud et al, 2014) concluded that cognitive impairment are inversely associated with QoL of elderly people with dementia, except for Monteiro et al (2014) and . These two studies failed to find a statistically significant association between cognitive status and QoL.…”
Section: Physical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…QoL is a multidimensional concept, which in older adults includes behavioural competence, the objective environment, psychological well-being, and perceived QoL (33). QoL among elderly persons with dementia is often diminished (34) due to several factors such as low cognitive function, major depression, lack of social activities, impaired mobility, and low performance in activities of daily living (26,(35)(36)(37). It is documented that older people consider good functioning to be of higher importance than the prevention of diseases (38), and PWDs with higher physical capabilities, such as strength and balance, have scored higher on QoL (26).…”
Section: Introductionmentioning
confidence: 99%
“…Det kan vaere vanskelig å tilpasse seg nye rutiner på et sykehjem, og noen opplever at sykehjemstilvaerelsen ikke oppfyller forventningene. De fleste er likevel fornøyde med hjelpen de får (11).…”
Section: Skreddersydde Løsningerunclassified